Splenogonadal Fusion Discovered by Testicular Torsion - Nahla Hmidi; Dorsaf Makhlouf; Rachida Laamiri; Nahla Kechiche; Badii Hmida; Amine Ksia; Lasaad Sahnoun; Mongi Mekki; Mohsen Belguith; Abdellatif Nouri (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Splenogonadal fusion, which is adherence of splenic tissue to gonads, is an uncommon congenital anomaly which mainly affects males. Herein, we report a case of splenogonadal fusion in a 20-month-old boy presenting with acute scrotal pain and inflammation. With the suspicion of left testicular torsion, an emergent left scrotal exploration was carried out. It revealed a necrotic left testicle along with a 360° rotation of the spermatic cord and three accessory structures in the lower pole of the testicle. Histology showed the presence of a splenic tissue. Splenogonadal fusion can present as an acute condition mimicking a testicular torsion. But, one should always bear in mind the possibility of this association. Splenogonadal fusion should be included in differential diagnosis of testicular mass to avoid unnecessary orchidectomy.